Quality of life : the assessment, analysis, and reporting of patient-reported outcomes - Fayers, Peter M.; Machin, David (Wiley Blackwell, 2016)
The assessment of patient reported outcomes and health-related quality of life continue to be rapidly evolving areas of research and this new edition reflects the development within the field from an emerging subject to one that is an essential part of the assessment of clinical trials and other clinical studies.